The Impact of Adaptive Leadership on Medical Team Performance in Emergency Units - Yuliaty, Farida; Amalia, Nafrah (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study investigates the influence of adaptive leadership style on the effectiveness of medical teams in emergency situations within the Emergency Unit. Employing a qualitative case study approach, the findings reveal that adaptive leadership positively contributes to team performance during critical incidents. Key characteristics of adaptive leaders—such as strategic thinking, empathetic engagement, and self-corrective learning—enhance nurse performance and overall team responsiveness. The study offers valuable insights for leadership development strategies in emergency healthcare settings.